1959
DOI: 10.1021/j150572a023
|View full text |Cite
|
Sign up to set email alerts
|

The Bismuth–Bismuth Trichloride System

Abstract: Vol. 63 as shown by the initial circled point on the curve in dows and examining the mica surfaces under the electron microscope, and Joseph Gabor, Bernard Girman and Norman Isaacs for assistance in the experimental work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

1965
1965
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 1 publication
2
24
0
1
Order By: Relevance
“…For Einstein calculations, the extrapolation to infinity of the relevant function in Eqs. (13) or (14) was performed by recording values of the function every 25 timesteps, and averaging all such values starting from t f = 1000 τ (4 ps). This averaging was done because the function values appear to oscillate aperiodically about an asymptote.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Einstein calculations, the extrapolation to infinity of the relevant function in Eqs. (13) or (14) was performed by recording values of the function every 25 timesteps, and averaging all such values starting from t f = 1000 τ (4 ps). This averaging was done because the function values appear to oscillate aperiodically about an asymptote.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…12 Equations (3) and (4) also nicely explained the conductivity maximum versus T at mild pressures that had been observed in other metal halide melts such as BiCl 3 . Bismuth chloride has a melting point of 232 • C, 13 a normal boiling point of 442 • C, 14 and a critical point of 905 • C. 15 Yosim and co-workers studied the dependence of molten BiCl 3 conductivity upon T, but along the more convenient "orthobaric" liquid/vapour coexistence curve rather than at constant p or V. This procedure allowed them to collect data over a larger liquid range than could be done at atmospheric pressures (initially 230-630 • C, 2 and later up to 960 • C 4 ). They found a maximum in σ at 425 • C, and a maximum in at 460 • C (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Obwohl man Subhalogenide auch bei den Alkali-und Erdalkalimetallen, beispielsweise CaCI-oder NaZC1-Spezies, diskutiert [75], werden Subhalogenide offenkundig bei der Untersuchung der Phasendiagramme von HgClz/Hg [85], CdClz/Cd [86] und BiC13/Bi [87] 2 N a C l + 2 C --f Na2C2+ C12 (3) Die …”
Section: Introductionunclassified
“…The Bi-BiClg system has been the object of numerous investigations, over the last 15 years, designed to elucidate the mechanism by which bismuth dissolves in bismuth tri chloride and to isolate and define the incongruently melting "Bid". The large solubility of metal in the salt, 45% Bi at 320°^ decreasing to 28% Bi at 550° and increasing to a consolute point at 51% Bi and 780°, was indicated in the phase diagram reported for the Bi-BiCl^ system (3). EMF (4), spectral (5) and vapor pressure (6) pretation of the solution mechanism at high metal concen trations (> 6.0 mole %).…”
Section: Introductionmentioning
confidence: 94%
“…Bi-BiClg, BiClg-AlClg, Bi-BiClg-AlClg) provide extensive evidence of mutual solubilities and compound formation.BiCl^ 167' which melts incongruently at 323°, has been shown to exist in condensed Bi-BiClg systems(3, 45, 46), and these same systems exhibit considerable solution of both metal in salt and salt in metal at high temperatures (a consolute point is reached at 780°, and 51 mol % Bi). Inthe BiClg-AlClg system Korshunov et al (47) have recently reported the existence of a 1:1 compound, BiClg-AlCl^ which melts congruently at 184°.…”
mentioning
confidence: 99%